Integrative DNA methylome analysis of pan-cancer biomarkers in cancer discordant monozygotic twin-pairs. Issue 1 (December 2016) - Roos, Leonie; van Dongen, Jenny; Bell, Christopher; Burri, Andrea; Deloukas, Panos; Boomsma, Dorret; Spector, Tim; Bell, Jordana
Abstract Background A key focus in cancer research is the discovery of biomarkers that accurately diagnose early lesions in non-invasive tissues. Several studies have identified malignancy-associated DNA methylation changes in blood, yet no general cancer biomarker has been identified to date. Here, we explore the potential of blood DNA methylation as a biomarker of pan-cancer (cancer of multiple different origins) in 41 female cancer discordant monozygotic (MZ) twin-pairs sampled before or after diagnosis using the Illumina HumanMethylation450 BeadChip. Results We analysed epigenome-wide DNA methylation profiles in 41 cancer discordant MZ twin-pairs with affected individuals diagnosed with tumours at different single primary sites: the breast, cervix, colon, endometrium, thyroid gland, skin (melanoma), ovary, and pancreas. No significant global differences in whole blood DNA methylation profiles were observed. Epigenome-wide analyses identified one novel pan-cancer differentially methylated position at false discovery rate (FDR) threshold of 10 % (cg02444695, P = 1.8 × 10−7 ) in an intergenic region 70 kb upstream of theSASH1 tumour suppressor gene, and three suggestive signals inCOL11A2, AXL, andLINC00340 . Replication of the four top-ranked signals in an independent sample of nine cancer-discordant MZ twin-pairs showed a similar direction of association atCOL11A2, AXL, andLINC00340, and significantly greater methylation discordance atAXL compared to 480 healthy concordant MZ twin-pairs. The effects at cg02444695 (nearSASH1 ), COL11A2, andLINC00340 were the most promising in biomarker potential because the DNA methylation differences were found to pre-exist in samples obtained prior to diagnosis and were limited to a 5-year period before diagnosis. Gene expression follow-up at the top-ranked signals in 283 healthy individuals showed correlation between blood methylation and gene expression in lymphoblastoid cell lines atPRL, and in the skin tissue atAXL . A significant enrichment of differential DNA methylation was observed in enhancer regions (P = 0.03). Conclusions We identified DNA methylation signatures in blood associated with pan-cancer, at or nearSASH1, COL11A2, AXL, andLINC00340 . Three of these signals were present up to 5 years prior to cancer diagnosis, highlighting the potential clinical utility of whole blood DNA methylation analysis in cancer surveillance.